2020
DOI: 10.15408/jch.v8i2.14854
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sri Hartini as The Regent of Klaten Related to The Corruption of Criminal Acts in Klaten District

Abstract: The administrators of the state should be obliged to carry out their duties with a sense of responsibility and do not commit disgraceful acts, without strings attached either for personal, family, crony or group interests and do not expect compensation in any form that is contrary to the provisions of the legislation in force. However, Sri Hartini as the state organizer as the Regent of Klaten did it against the law. For this reason, the purpose of this research is how is the role of Sri Hartini as the Regent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In a study by (Rizqi et al, 2020) which examined criminal acts of corruption, gratification, bribery, and abuse of authority by the Regent of Klaten, it was found that there is a network that is a liaison between various elements in the Klaten Regency. In the case of this research, it was also found a network that became a link between various parties, Muhammad Tamzil would not be able to carry out this act of corruption without a strong network, there were 2 important people who became the liaison between Muhammad Tamzil and the givers, thanks to this network, there are many actors involved in this case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by (Rizqi et al, 2020) which examined criminal acts of corruption, gratification, bribery, and abuse of authority by the Regent of Klaten, it was found that there is a network that is a liaison between various elements in the Klaten Regency. In the case of this research, it was also found a network that became a link between various parties, Muhammad Tamzil would not be able to carry out this act of corruption without a strong network, there were 2 important people who became the liaison between Muhammad Tamzil and the givers, thanks to this network, there are many actors involved in this case.…”
Section: Discussionmentioning
confidence: 99%
“…The network in an act of corruption is almost always there, there can be many or only a few actors involved, they support each other with the same goal of seeking profit. Networks or actors in this case are actors involved and have their respective roles, can be formed through pre-existing relationships, cooperation, and also transfer of resources (eg bribery) (Rizqi et al, 2020).…”
Section: Mapping Of Actors and Their Roles In Corruption Crimesmentioning
confidence: 99%
“…This research intended to answer these problems. This research used the Klaten Regency government as the unit of analysis because Klaten Regency has been in the public and media spotlight due to corruption and dynastic politics for the last two decades (Rizqi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%